Education of the Left-behind Children of Migrant Labourers of Balangir An Overview - Nahak, Prasant kr.; Singh, Meenakshi (JOURNAL OF INDIAN EDUCATION, 2019)
Seasonal migration of labourers in search of livelihood is a common phenomenon in western Odisha. Kalahandi, Balangir, Bargarh and Nuapada are the major migration prone districts of western Odisha. Each year these districts witness millions of labourers who migrate. They migrate every year from October to May for working in brick kilns across different states. The district of Balangir alone sends more than one lakh migrant labourers each year, which includes approximately 35% children. They usually take their children of school-going age with them as they have no one to look after if left behind. This seriously affects the education of the children, resulting in low achievements and dropouts. To sort this out, seasonal hostels are in operation in all the migration prone blocks of Balangir district. They provide the basic facilities like food and lodging to children of migrant labourers for the time they are working as migrant labourers. This study is an attempt to identify the lacunae in these facilities and the administration related problems faced by the seasonal hostels.